Peran Keluarga dalam Mencegah Stunting - Rizki Amalia; Mutmainnah Mutmainnah (Departement of Mathematics Education, 2024)
Stunting is a chronic nutritional issue that significantly affects the physical growth and development of children. Families play a crucial role in preventing stunting through various means. Ensuring adequate nutrition, understanding proper dietary practices, and actively monitoring a child's growth and development are key aspects of stunting prevention within the family. Furthermore, emotional support and family education also contribute to reducing risk factors that can lead to stunting, such as stress and imbalanced eating habits. Therefore, the family's role in creating a healthy, supportive, and educational environment is paramount in addressing stunting issues and enhancing the quality of life for children.